2012
DOI: 10.1016/j.biortech.2012.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of single-stage and two-stage anaerobic digestion for the treatment of thin stillage

Abstract: a b s t r a c tA comparative evaluation of single-stage and two-stage anaerobic digestion processes for biomethane and biohydrogen production using thin stillage was performed to assess the impact of separating the acidogenic and methanogenic stages on anaerobic digestion. Thin stillage, the main by-product from ethanol production, was characterized by high total chemical oxygen demand (TCOD) of 122 g/L and total volatile fatty acids (TVFAs) of 12 g/L. A maximum methane yield of 0.33 L CH 4 /gCOD added (STP) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(59 citation statements)
references
References 29 publications
2
51
2
4
Order By: Relevance
“…However, the higher gross energetic potential was due to the higher performance in Total biogas production = 3946 ml Total biogas production = 4220 ml Total biogas production = 4145 ml Total biogas production = 3943 ml Total biogas production = 3819 ml Total biogas production = 3777 ml Total biogas production = 3103 ml Total biogas production = 4072 ml the methanogenic reactor rather than the hydrogen production from the fi rst stage. Nasr et al (2012) estimated the energy balance of two-stage anaerobic digestion of thin stillage, and concluded that optimizing the two-stage anaerobic digestion process can increase the energy balance by 18.5%. Lu et al (2008) reported that a two-stage reactor showed a better energy balance with a surplus of 2.17 kJ/d, as compared to a single stage system for treating sewage sludge.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…However, the higher gross energetic potential was due to the higher performance in Total biogas production = 3946 ml Total biogas production = 4220 ml Total biogas production = 4145 ml Total biogas production = 3943 ml Total biogas production = 3819 ml Total biogas production = 3777 ml Total biogas production = 3103 ml Total biogas production = 4072 ml the methanogenic reactor rather than the hydrogen production from the fi rst stage. Nasr et al (2012) estimated the energy balance of two-stage anaerobic digestion of thin stillage, and concluded that optimizing the two-stage anaerobic digestion process can increase the energy balance by 18.5%. Lu et al (2008) reported that a two-stage reactor showed a better energy balance with a surplus of 2.17 kJ/d, as compared to a single stage system for treating sewage sludge.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…On the other hand, in a one-stage process both the acidogenic step and the methanogenic step are mixed in one reactor, which results low process stability due to susceptible to pH and temperature fluctuations, overloading, acid accumulation, etc. Some studies (Vinas et al 1993;Lehtomäki et al 2008;Nasr et al 2012) claimed that a twostage digestion system would result in a greater yield of methane over the one-stage system due to a larger fraction of the substrates being converted to biogas by the more vigorous activity of the acidogenic microbes in the first stage of the two-stage system. Nasr et al (2012) reported a comparative analysis on the efficiency of single-stage and two-stage digestion systems using thin stillage as the substrate and revealed that an improved energy yield of 18.5% was achieved through two-stage systems.…”
Section: Comparison Of Reactor Configurationsmentioning
confidence: 99%
“…Some studies (Vinas et al 1993;Lehtomäki et al 2008;Nasr et al 2012) claimed that a twostage digestion system would result in a greater yield of methane over the one-stage system due to a larger fraction of the substrates being converted to biogas by the more vigorous activity of the acidogenic microbes in the first stage of the two-stage system. Nasr et al (2012) reported a comparative analysis on the efficiency of single-stage and two-stage digestion systems using thin stillage as the substrate and revealed that an improved energy yield of 18.5% was achieved through two-stage systems. Lehtomäki et al (2008) investigated anaerobic digestion of grass silage in leach bed reactors with and without a second stage UASB reactor and found that 66% of the total methane potential in grass silage was obtained in the two-stage process whereas in the one-stage process only 20% of the methane potential was extracted.…”
Section: Comparison Of Reactor Configurationsmentioning
confidence: 99%
“…The separation of the acidogenic step from the methanogenic one results in enhanced stability to the different groups of microorganisms as well as in a better process control [116]. Nasr et al [106] compared one-stage and two-stage anaerobic digestion processes for the treatment of thin stillage. The separation of acidogenesis and methanogenesis allowed a maximum methane yield of 0.33 L/gCOD added and an overall increase of 18.5% in the energy yield.…”
Section: The Combination Of Bioethanol and Biogas Production Processesmentioning
confidence: 99%